Sobre o teor de vitamina C em mirtáceas: Parte II - Brume, Walter; O Silva, Daison; Mattos, João (Revista Ceres, 2025)
According to the present experiments there is a notable effect of the toxic oxalic acid as a protecting solution for vitamin C. The opposite is true of the non-toxic citric acid.